Long-term trends in home advantage in professional team sports in North America and England (1876-2003) - Pollard, R.; Pollard, G. (Journal of Sports Sciences, 2005)
Home advantage is quantitatively defined and calculated for each season since the start of the main professional sports in North America and England. Over 400,000 games are analysed. The leagues represented are the National League (1876-2002) and American League (1901-2002) for baseball, the National Hockey League (1917-2003) for ice hockey, the National Football League (1933-2002) for American football, the National Basketball Association (1946-2003) for basketball, and the four levels of professional football, formerly called the Football League, in England (1888-2003). Problems caused by unbalanced playing schedules are considered. The results are presented graphically to show long-term trends and sudden changes. The highest levels of home advantage for all sports were in their early years of existence. Home advantage in ice hockey, basketball and football in England has declined over the last two decades. In baseball there has been very little change over the last 100 years, with home advantage consistently lower than in other sports. There was a large drop in home advantage in football in England following the 7-year suspension of the league during the Second World War. The trends and changes provide some evidence that travel and familiarity contribute to home advantage, but little in support of crowd effects.